Refleksi Filsafat Sosial Ibnu Sina dalam Pendidikan Holistik untuk Memperkuat Moral Remaja di Indonesia - Noneng Siti Nurhasanah (Gunung Djati Conference Series, 2023)
This study aims to discuss the reflection of Ibnu Sina's social philosophy in holistic education to strengthen the morale of adolescents in Indonesia. This research uses a qualitative approach by applying descriptive-analytical methods. The formal object of this study is Ibn Sina's theory of holistic education, while the material object is a reflection of social philosophy. Holistic education becomes a locus or scope that becomes a container (space) for the discovery of reflection on social philosophy. The rest, the context of this research is to strengthen the morale of adolescents in Indonesia. The results and discussion in this study show that the moral problems of adolescents in Indonesia cannot be ignored, one of the alternative solutions offered is education, especially Ibnu Sina's holistic education which provides an initial foundation in strengthening the morale of adolescents in Indonesia. This study concludes that holistic education can be used as an alternative to strengthen the morale of adolescents in Indonesia. This study recommends to educational institutions and organizations as well as the community to pay more attention to moral problems that occur today, especially the morals of adolescents in Indonesia. Through strong morals, it is hoped that the quality of Indonesian society will increase.